Methods of scientific analysis of corruption relations - M. V. Shedij (Управленческое консультирование)
Monitoring of the level of corruption in Russia both by region and by levels of power, by specific government institutions and by certain spheres of social activity is one of the most important components of the Russian national anti-corruption policy, including its research component. In recent decades, there has been a significant increase in empirical studies of the phenomenon of corruption, which is largely due to the ever growing interest of domestic and foreign (national and international) research centers to conduct empirical studies of the quantitative and qualitative characteristics of corruption and to find more effective ways to counteract this phenomenon.Unlike other types of crimes, corruption is deeply latent in connection with what for a long time the only source of information about corruption was criminal statistics. However, comparative study of the phenomenon of corruption both in a single country and on a regional and, even more so, global scale, on the basis of official statistics is practically impossible, since the registration of cases of corruption in official statistics is incomplete, fragmentary. In addition, a large number of statistically recorded misconduct can not always be interpreted as an indicator of high corrupt society.The article analyzes the scientific methods of diagnosing corrupt relations in the modern society, their specificity, advantages and disadvantages in monitoring corruption are examined.